Determinants of service export in selected developing Asian countries - Ahmad, Siti Aisah; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (Universiti Malaysia Sarawak, 2017)
This paper attempts to empirically examine the determinants of service export in selected developing Asian countries (China, Hong Kong, South Korea, India, Iran, Indonesia, Malaysia, Philippines, Singapore, Thailand, Kuwait, Saudi Arabia and Turkey). The study conducted a static linear panel data analysis on annual data covering the period of 1985-2012. The main finding indicates that exchange rate, foreign income, foreign direct investment (FDI), the value added by services and communication facilities are likely to influence services exports in the selected developing Asian countries. This suggests that these countries have the opportunity to compete globally by exporting services, provided that they are able to exploit and enhance their potential by focusing on the significant and relevant indicators.